CARÁCTERÍSTICAS DE CALIDAD DE LA FIBRA DE VICUÑAS PERUANAS - Olaguivel Flores, César Augusto; Bujaico, N.; Mamani Cato, Rubén Herberht; Huaman, L. (VIII Congreso Mundial Sobre Camélidos, 2021)
2 Páginas